I am trying to understand how to go about answering this question...
So far I have (which I am in no way confident about):
- When n=1, we have 1^2=1 and (1+1)(2^1+1)(2^1+3)/3=10
Is this the way to go about this?
Any help in the right direction would be very appreciated.
The answer to this question... View the full answer
Sign up to view the full answer
To prove by induction, show that the formula works for n = 1, and that if the formula works for n, then it must work for n +... View the full answer
- The second last line of the answer has a typo and should be: (4n^3 + (12+12)n^2 + (11+36)n + (3+27)) / 3 = (4n^3 + 24n^2 + 47n + 30) / 3
- May 07, 2018 at 12:30am